2015
DOI: 10.1080/19440049.2015.1027746
|View full text |Cite
|
Sign up to set email alerts
|

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans

Abstract: Fumonisins (FB) are mycotoxins found in maize. They are hypothesised risk factors for neural tube defects (NTDs) in humans living where maize is a dietary staple. In LM/Bc mice, FB1-treatment of pregnant dams induces NTDs and results in increased levels of sphingoid base 1-phosphates in blood and tissues. The increased level of sphingoid base 1-phosphates in blood is a putative biomarker for FB1 inhibition of ceramide synthase in humans. Collection of blood spots on paper from finger sticks is a relatively non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 31 publications
4
63
0
Order By: Relevance
“…Are the positive correlations between UFB 1 levels, calculated FB intake, and Sa 1‐P concentration and Sa 1‐P/So 1‐P ratio proof that FB inhibits CerS in humans consuming diets containing high levels of FB? Primary cultures of human neural progenitor cells respond to FB 1 treatment by accumulating large amounts of Sa and Sa 1‐P and much lesser amounts of So and So 1‐P , similar to what has been reported in numerous animal studies and attributed to de novo CerS inhibition as first demonstrated by Wang et al. .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Are the positive correlations between UFB 1 levels, calculated FB intake, and Sa 1‐P concentration and Sa 1‐P/So 1‐P ratio proof that FB inhibits CerS in humans consuming diets containing high levels of FB? Primary cultures of human neural progenitor cells respond to FB 1 treatment by accumulating large amounts of Sa and Sa 1‐P and much lesser amounts of So and So 1‐P , similar to what has been reported in numerous animal studies and attributed to de novo CerS inhibition as first demonstrated by Wang et al. .…”
Section: Discussionsupporting
confidence: 83%
“…Based on the unique functional and metabolic characteristics of So 1‐P in blood, and in particular the fact that RBC cannot make Sa or metabolize Sa 1‐P, we hypothesized that blood spots from Guatemalan women living in areas where FB exposure is high would show higher Sa 1‐P/So 1‐P ratios when compared to populations living in low exposure areas, reflecting the increased Sa produced in cells and tissues as a consequence of FB‐induced CerS inhibition. Consistent with this hypothesis would be elevated concentrations of Sa 1‐P in the blood spots as we have seen in mice . In mice the levels of Sa 1‐P in the RBC closely paralleled the levels of Sa seen in liver and kidney and the UFB 1 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When droplet of capillary blood is directly deposited on the filter paper, the volume of this blood cannot be precisely controlled and inaccuracies in quantification values can be obtained due to differences in hematocrit. In the literature, different strategies to overcome this drawback have been proposed, such as the use of volumetric absorptive microsampling (VAMS) or the photometric measurement of the protein content . In the present study, a simplified strategy to quantify the phenolic metabolites was tested, assuming a linear relation between volume of blood applied and the area of the premarked DBS circle.…”
Section: Resultsmentioning
confidence: 61%